2021
DOI: 10.2147/orr.s321893
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Management of Meniscal Cysts: A Systematic Review

Abstract: Purpose The purpose of this study was to systematically review the outcomes of arthroscopic management of meniscal cysts and to compare the results across the reported surgical techniques. Methods Following the PRISMA methodology, 3 databases (PubMed, Scopus and Web of Science) were searched from inception to June 2021 for randomized controlled trials (RCTs) and observational studies reporting outcomes on patients with meniscal cysts who underwent arthroscopic surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
(138 reference statements)
0
2
0
Order By: Relevance
“…Giant meniscal cyst management raises considerable controversy 15 , as some clinicians still believe that conservative management with follow‐up is the best option for asymptomatic cases. Traditional treatment, including open cystectomy, complete or partial meniscectomy, arthroscopic meniscus repair, and cyst excision, is the best method of management.…”
Section: Discussionmentioning
confidence: 99%
“…Giant meniscal cyst management raises considerable controversy 15 , as some clinicians still believe that conservative management with follow‐up is the best option for asymptomatic cases. Traditional treatment, including open cystectomy, complete or partial meniscectomy, arthroscopic meniscus repair, and cyst excision, is the best method of management.…”
Section: Discussionmentioning
confidence: 99%
“…Co-existing meniscal tears, if found, were mostly debrided until a stable rim was achieved ( 4 , 15 - 17 ). A recent systematic review by Haratian et al ( 18 ) showed that arthroscopic management of cysts can provide satisfactory outcomes for patients with good return to sport. However, it is not clear whether the treatment of the co-existing meniscal tears can affect the outcomes achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Описані різні методики артроскопічної декомпресії. Ранні артроскопічні процедури в основному були зосереджені на простій евакуації вмісту кісти в порожнину суглоба [9,10]. Черезшкірна декомпресія за допомогою голки малого .…”
unclassified
“…У цьому огляді середньозважений показник за шкалою Лайзхольма для всіх артроскопічних процедур становив 77,7 бала, і в нього були включені майже всі дані про кісти латерального меніска. Найбільшу вагу для розрахунку середньозважених балів за шкалою Лайзхольма в цьому огляді мали дані одного дослідження, які повідомили про 72,4 та 74 бали за шкалою Лайзхольма для артроскопічної декомпресії та висічення відповідно [18].…”
unclassified